Preventive Effect of blueberries on Diethylnitrosamine-Induced Hepatocarcinogenesis in Rats - El-gamal, El-Khedr Mohamed Mostafa (Journal of medical and pharmaceutical sciences, 2017)
Nitrosamine compounds are known hepatic carcinogens. This study was designed to study the efficacy of dietary supplementation with blueberries (BB) on diethylnitrosamine (DEN)-initiated hepatocarcinogenesis in male wistar rats. Rats were divided into three groups. The first group served as normal control group, the second group received DEN at a dose of 10 mg/kg body weight five times a week for 15 weeks. The third one received DEN as in DEN-treated group simultaneously with 4% BB-supplemented diet. The results showed that BB caused significant decrease in the elevated serum levels of α-fetoprotein (AFP), homocysteine (Hcy) along with levels of glutathione(GSH), deoxyribonucleic acid (DNA), ribonucleic acid (RNA)and activity of glutathione reductase (GR) in liver. Normalization of elevated 2-macroglobulin (2M) and total antioxidant capacity (TAC) levels in serum, hepatic Glutathione-S-transferase (GST), glutathione peroxidase (GPx) activities and liver weight was achieved whereas body weight was significantly decreased. Moreover, no significant change was observed in elevated relative liver weight, hepatic glucose-6-P-dehydrogenase (G6PD), lactate dehydrogenase (LDH) along with serum aminotransferases, alkaline phosphatase (ALP) and ɤ -glutamyltransferase (ɤ-GT) activities. Significant increase in reduced hepatic activity of xanthine oxidase (XO) was achieved and histopathological damage was minimized in BB-treated group. It is suggested that BB suppress DEN-induced hepatocarcinogenesis and could be developed as a promising chemoprotective natural supplement for liver cancer.
Keywords: blueberries (BB); diethylnitrosamine; hepatocarcinogenesis; rats; α2-macroglobulin; α -fetoprotein; homocysteine; glutathione